2020
DOI: 10.3390/toxins12060404
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxins and Vascular Dysfunction

Abstract: Vascular dysfunction is an essential element found in many cardiovascular pathologies and in pathologies that have a cardiovascular impact such as chronic kidney disease (CKD). Alteration of vasomotricity is due to an imbalance between the production of relaxing and contracting factors. In addition to becoming a determining factor in pathophysiological alterations, vascular dysfunction constitutes the first step in the development of atherosclerosis plaques or vascular calcifications. In patients with CKD, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 205 publications
(256 reference statements)
1
49
0
Order By: Relevance
“…Accordingly, chronic exposure of blood vessels to uremic toxins increases NADPH activity and the ensuing ROS overproduction whilst simultaneously downregulating key antioxidative enzymes such as the endothelial nitrous oxide synthases (eNOS) and superoxide dismutases (SODs). Aberrantly produced ROS act on the cells of the underlying medial layer promoting the osteogenic trans differentiation of VSMCs [reviewed in [ 57 ]]. An additional effect of uremic toxins on ECs is the induction of matrix metalloproteinase 2 and 9 (MMP-2 and -9) and the downregulation of the tissues inhibitors of metalloproteinases 1 and 2 (TIMP-1 and TIMP-2) that result in increased extracellular matrix degradation [ 58 ].…”
Section: Uremic Toxin Mediated Pathways Leading To Vascular Calcifmentioning
confidence: 99%
“…Accordingly, chronic exposure of blood vessels to uremic toxins increases NADPH activity and the ensuing ROS overproduction whilst simultaneously downregulating key antioxidative enzymes such as the endothelial nitrous oxide synthases (eNOS) and superoxide dismutases (SODs). Aberrantly produced ROS act on the cells of the underlying medial layer promoting the osteogenic trans differentiation of VSMCs [reviewed in [ 57 ]]. An additional effect of uremic toxins on ECs is the induction of matrix metalloproteinase 2 and 9 (MMP-2 and -9) and the downregulation of the tissues inhibitors of metalloproteinases 1 and 2 (TIMP-1 and TIMP-2) that result in increased extracellular matrix degradation [ 58 ].…”
Section: Uremic Toxin Mediated Pathways Leading To Vascular Calcifmentioning
confidence: 99%
“…Uremic toxins can lead to endothelial dysfunction, vascular senescence, vascular inflammation in CKD patients. It is supporting the link between uremic toxins and vascular dysfunction 32 . Silvia D et al demonstrated that uremic toxins impaired the autophagic flux leading to endothelial dysfunction 33 .…”
Section: The Relationship Between Gut Microbiota‐derived Metabolites mentioning
confidence: 77%
“…One mechanism involves the intracellular generation of oxidative stress [ 57 ]. Indeed, it has been reported that exposure to several well-known UTs (including inorganic phosphate, pCS, IxS, and FGF23) leads to vascular dysfunction [ 58 ].…”
Section: Discussionmentioning
confidence: 99%